Postoperative cognitive dysfunction in noncardiac surgery: A review. (February 2019) - Green, Christopher M.; Schaffer, Susan D.
Abstract: Postoperative Cognitive Dysfunction (POCD) following noncardiac surgery is an underappreciated phenomenon. Researchers consistently find incidence rates around 25% in the first several weeks following noncardiac surgery in elderly patients, and the condition is associated with decreased quality of life, higher healthcare costs, and increased mortality. Despite the frequency and magnitude of its complications, POCD is seldom diagnosed outside of research settings. POCD is loosely defined as a decline in cognitive function following surgery, however, there is currently no consensus on diagnostic criteria for POCD. Proposed etiologies to explain POCD in noncardiac surgery have included the effects of centrally acting anesthetics, Alzheimer's pathology exacerbated perioperatively, changes in neuroreceptor function, and the effects of surgical trauma on cerebral endothelium. However, no single entity has garnered universal support as a single causative factor and the development of POCD likely involves a complicated interaction between patient- and procedure-related variables. Although inhaled anesthetics have been implicated in the development of POCD, any benefits seen with total intravenous anesthesia and regional techniques fade within the first postoperative week, regional cerebral oxygen saturation and processed encephalogram monitoring have produced contradictory findings, and no pharmaceutical adjunct or anesthetic technique has consistently decreased POCD rates. Therefore, the best evidence-based recommendations for preventing POCD are to reduce the inflammatory response to surgery through less invasive surgical approaches when possible and providing adequate analgesia to minimize the stress response. Those at risk for POCD should be provided candid counselling preoperatively so that cognitively demanding tasks can be accomplished before surgery and postoperative assistance arranged. Fortunately, POCD is usually self-limiting and cognitive performance improves during the first several months postoperatively, but there are no evidence-based treatment strategies to hasten recovery. The time has come for the perisurgical community to transition POCD from an entity confined to research settings with updated informed consents that note the possibility of post-operative cognitive decline, pre and post-operative cognitive testing for at-risk individuals, and routine referral for continuing care when post-operative deficits are identified. Highlights: POCD affects 25-40% of elderly, noncardiac surgical patients in the early postoperative period. The condition is associated with decreased quality of life, and increased mortality within the first year of surgery. The etiology is unclear, but failed resistance of neurologic endothelium to maintain homeostasis after trauma is likely. Advanced age, a declining preoperative cognitive trajectory, and more invasive surgeries are risk factors. Prevention strategies have only demonstrated benefit within the first week of surgery.